Attitude towards seeking psychological help regarding psychiatric symptoms and stigma in patients with fibromyalgia - Bulu, A.; Onalan, E.; Korkmaz, S.; Yakar, B.; Karatas, T. K.; Guven, T.; Donder, E. (Verduci Publisher, 2023)
OBJECTIVE: The current study aimed to examine the psychiatric symptoms that can be seen in fibromyalgia (FM) patients, their attitudes toward seeking psychological help, and their concerns about stigma. Besides, it was investigated whether the stigma concerns that they may experience about receiving psychiatric treatment constitute an obstacle for patients to receive psychiatric treatment. SUBJECTS AND METHODS: This cross-sectional descriptive study was conducted between February and July 2020. Various seeking help were measured with Attitude Towards Seeking Psychological Help Scale-Short Form (ATSPPH-SF), Self-Stigma in the Process of Seeking Psy-chological Help Scale (SSPSPHS), Intention to Seek Psychological Help Inventory (ISPHI), and Social Stigma Due to Seeking Psychological Help Scale (SSDSPHS). FM symptoms of pa-tients were measured with The Symptom Screen-ing Questionnaire, Revised 90 Items (SCL-90-R). Quality-of-life parameters were measured with Fibromyalgia Impact Questionnaire (FIQ).RESULTS: Fibromyalgia patients had higher somatization (p=0.001), psychotism (p=0.045) and phobic anxiety (p=0.015) scores than controls. The ATSPPH-SF (p=0.002) and SSPSPHS (p=0.043) scale scores of the FM patients were higher than the controls. There was a significant positive correlation between FIQ and SSPSPHS (r=0.288, p=0.043) and SCL-90 overall (r=0.602, p<0.001) and all subscales scores. Patients with high active psychotic symptom levels had high-er FM exposure scale scores and SCL-90 over-all scores than those with low active psychotic symptom levels (p<0.001).CONCLUSIONS: The findings of this study showed that fibromyalgia patients have more somatization symptoms than healthy individuals, and as psychiatric symptoms increase in these individuals, their level of being affected by FM increases.
Keywords: Fibromyalgia; Social stigma; Seeking-help; Attitude; Quality of life